PESANTREN-BASED EXPERIENTIAL MARKETING; SENSE EMOTIONAL ANALYSIS IN BUILDING CUSTOMER LOYALITY - Mundiri , Akmal; Firdausy, Arij (Universitas Nurul Jadid, 2022)
This research aims to produce Pesantren-based experiential marketing; emotional sense analysis in building customer loyalty. The research approach used is a qualitative approach with a case study type. The data that has been collected is analyzed by using the Miles and Huberman data analysis technique which consists of data reduction, data display, and verification. The results of this study indicate that the process of experiential marketing is based on Pesantrens; emotional sense analysis in building customer loyalty is carried out through the provision of stimuli and cognitive consistency. Providing stimuli in Pesantren-based experiential marketing is carried out with osabar, ospectren, and harlah events. Meanwhile building cognitive consistency is done by Exemplary of Kyai, organizational climate and culture of pesantren, and spiritual experience. Dengan demikian, penelitian ini menemukan teori tentang marketing based on spiritual experience.